Seed Priming: A Potential Supplement in Integrated Resource Management Under Fragile Intensive Ecosystems - Devika, O. Siva; Singh, Sonam; Sarkar, Deepranjan; Barnwal, Prabhakar; Suman, Jarupula; Rakshit, Amitava (Frontiers in Sustainable Food Systems, 2021)
A majority of agricultural activities are conducted under fragile lands or set up. The growth and development of crops are negatively affected due to several biotic and abiotic stresses. In the current situation, research efforts have been diverted towards the short-term approaches that can improve crop performance under changing environments. Seed treatment or priming technology is in a transition phase of its popularity among the resource-poor farmers. Suitable policy intervention can boost low-cost techniques to implement them on a larger scale in the developing countries and harness the maximum benefits of sustainable food production systems. Primed seeds have high vigour and germination rate that helps in seedling growth and successful crop stand establishment under stress conditions. This review is attempted to assess different seed priming techniques in terms of resource use efficiency, crop productivity, cost-benefit balance, and environmental impacts. Moreover, an in-depth study of the mechanisms (physiological and biochemical) of seed priming is also elaborated. A comprehensive study of the applications of priming technology under diverse agro ecosystems can light our understanding of the adaptive management of natural resources.